Prototipo de un sistema remoto de seguridad en el hogar - Villegas Villada, Daniel (Universidad de San Buenaventura-Cali, 2017)
From the moment man began to make advances in the field of electronics, he has sought ways to improve his way of life both in comfort and safety. For this reason, more and more electronic systems are being developed that operate in workplaces and homes, among other places.The development of this document describes the design of a Remote Monitoring and Control System for Fire, Smoke and Gas Leaks, which allows a safer environment for residents of said dwelling and which consists of different sensors which will be supervising the Variables determined by the research carried out. By obtaining the data provided by the sensors, you can know if there is an imminent danger in the house, and if this is the case, preventive systems such as sprinklers, solenoid valves and extractors will be implemented to prevent further damage. In turn a text message will be sent to the cell phone of the registered user, informing him that danger has been generated in the house so that it communicates with the corresponding authorities